2015
DOI: 10.1039/c4ta05316h
|View full text |Cite
|
Sign up to set email alerts
|

Solvothermal synthesis and electrochemical charge storage assessment of Mn3N2

Abstract: Mn3N2nanocapsules and nanoparticulates are prepared under solvothermal conditions and evaluated in aqueous supercapacitor electrode (KOH electrolyte) and lithium or sodium battery negative electrode applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…3 Hence the literature on negative electrode materials has been dominated by amorphous "hard" carbons, alloys with elements such as Sn and Sb, and oxides. 4 Recently a number of transition metal nitrides have shown promising performance as sodium battery negatives, including work by ourselves on Ni 3 N, 5 Cu 3 N 6 and Mn 3 N 2 , 7 and by Cui et al on VN. 8 These operate by a conversion mechanism at the particle surfaces, with reduction of the metal nitride to the metal, presumably with amorphous sodium nitride also formed.…”
Section: Introductionmentioning
confidence: 99%
“…3 Hence the literature on negative electrode materials has been dominated by amorphous "hard" carbons, alloys with elements such as Sn and Sb, and oxides. 4 Recently a number of transition metal nitrides have shown promising performance as sodium battery negatives, including work by ourselves on Ni 3 N, 5 Cu 3 N 6 and Mn 3 N 2 , 7 and by Cui et al on VN. 8 These operate by a conversion mechanism at the particle surfaces, with reduction of the metal nitride to the metal, presumably with amorphous sodium nitride also formed.…”
Section: Introductionmentioning
confidence: 99%
“…Among these chemical techniques [24,25], the solvothermal process has attracted a great deal of attention since particles with the desired characteristics can be prepared with this technique by controlling the solution pH, reaction temperature, reaction time, solute concentration and solvent types, depending on the particular application [26]. The main advantages of solvothermal synthesis are related to homogeneous nucleation processes, ascribed to elimination of the calcinations step to produce very low grain sizes and high purity powders [27]. Besides the association of microwave radiation to solvothermal method generates a physical-chemical hydride synthesis methodology [28].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that titanium nitride can be reduced to the metal in lithium batteries, 85 but its storage mechanism in sodium batteries is not clear. Research in our group [10][11][12][13] has shown that in several cases only the surface of metal nitrides reacts, and the small variations seen here suggest that TiN has only reacted in the surface region during cycling vs sodium.…”
Section: Figmentioning
confidence: 61%
“…5,6 A series of transition metal nitrides (Cu3N 7 , Co3N 8 and Fe3N 8 ) and transition metal carbide (Mo2C 9 ) have been explored as anode materials for lithium ion batteries (LIBs) and recently a number of metal nitrides (MNx, M = Cu, Mn, Ni, Sn etc.) synthesized by our group [10][11][12][13] and the VN reported by Cui et al 14 have shown promising electrochemical properties for sodium ion batteries. In several of these systems there is evidence that conversion reactions (reduction to the metal and sodium nitride) occur mainly at particle surfaces and hence that reducing particle size will be important in maximizing their capacities.…”
Section: Introductionmentioning
confidence: 97%